CORPUS FOR LANGUAGE TEACHING: STUDENTS' PERCEPTIONS AND DIFFICULTIES - Ikmi Nur Oktavianti; Arilia Triyoga; Icuk Prayogi (PROJECT (Professional Journal of English Education), 2022)
Regarding the seemingly ignored corpus for pedagogical contexts, it is necessary to investigate how prospective English teachers perceive corpus and its use for language teaching. From the description of the perceptions, it is then possible to consider further pedagogical implementation. This study thus examines English Education Department students' perceptions of corpus use for English language teaching in the Indonesian context. There are 31 participants from the fifth-semester students of an English Education Department in Yogyakarta, Indonesia. The perception data were collected through questionnaires and interviews after some practice of corpus use. The questionnaires and interviews show that most students perceived corpus positively and found corpus application for language teaching beneficial and essential, albeit unfamiliar with corpus. Due to ignorance, there are some difficulties faced by the students. However, this study shows the advantages of using corpus for teaching language outweighed the challenges. Thus, it should be considered to equip students in language education departments with corpus lessons intensively.